Modeling a Quality of Experience aware distance educational system - Vasileva-Stojanovska, Tatjana; Trajkovikj, Vladimir (Springer International Publishing, 2014)
A successful distance educational system has to provide certain commonly accepted educational objectives in order to assure its high acceptability and successful implementation. One of the main objectives of any distance educational system is to bring the educational material and its presentation closer to the individual student's needs thus delivering high Quality of Experience (QoE). The overall QoE is a subjective perception impacted by factors from objective technical nature and subjective nature. In this paper we propose few educational scenarios that enable dynamical presentation of educational services and content delivery to the students depending on their personal affinities. Students can choose the preferred media presentation and after completion of the course an evaluation and comparison of the student’s performances on the different educational scenarios is made. The aim of the study is to explore the impact of the Quality of Experience (QoE) on the performance and thus the overall Quality of Learning (QoL) of students. For comparative analysis of the educational scenarios, t-test statistic is proposed. In addition, we propose a neuro fuzzy inference system for QoE evaluation, utilizing an ANFIS controller to compare and predict the expected QoE based on the input parameters affecting the QoE. The model should provide an aid to design of educational courses and media presentation in a way that aims toward student satisfaction and educational benefits for the current and future users of distance educational systems. This paper is focused on the description of the proposed QoE aware educational system, leaving the discussion of the experimental results for future work.
Keywords: distance education, quality of experience, quality of learning